Adsorption And Kinetic Study Of Cocoa Pod Husk Activated Carbon On Dyes - Kasma Jeru (School of Environmental Engineering, Universiti Malaysia Perlis, 2015)
It is important to treat aqueous solution contaminated with dye, focusing specially on methylene blue and methyl orange. The objectives of this study are stated as follows to prepare and characterize the cocoa pod husk as activated carbon. To evaluate the efficiency of cocoa pod husk activated carbon for the adsorption of dyes. To study the effect of dosage, contact time, effect of pH , initial dye concentration, adsorption isotherm, and kinetic parameters of the adsorption.